An ERP study of recognition memory for concrete and abstract pictures in school-aged children - Boucher, Olivier; Muckle, Gina; Chouinard-Leclaire, Christine; Westerlund, Alissa; Burden, Matthew J.; Jacobson, Sandra W.; Jacobson, Joseph L. (International Journal of Psychophysiology, 2016)
Recognition memory for concrete, nameable pictures is typically faster and more accurate than for abstract pictures. A dual-coding account for these findings suggests that concrete pictures are processed into verbal and image codes, whereas abstract pictures are encoded in image codes only. Recognition memory relies on two successive and distinct processes, namely familiarity and recollection. Whether these two processes are similarly or differently affected by stimulus concreteness remains unknown. This study examined the effect of picture concreteness on visual recognition memory processes using event-related potentials (ERPs). In a sample of children involved in a longitudinal study, participants (N=96; mean age=11.3years) were assessed on a continuous visual recognition memory task in which half the pictures were easily nameable, everyday concrete objects, and the other half were three-dimensional abstract, sculpture-like objects. Behavioral performance and ERP correlates of familiarity and recollection (respectively, the FN400 and P600 repetition effects) were measured. Behavioral results indicated faster and more accurate identification of concrete pictures as "new" or "old" (i.e., previously displayed) compared to abstract pictures. ERPs were characterized by a larger repetition effect, on the P600 amplitude, for concrete than for abstract images, suggesting a graded recollection process dependent on the type of material to be recollected. Topographic differences were observed within the FN400 latency interval, especially over anterior-inferior electrodes, with the repetition effect more pronounced and localized over the left hemisphere for concrete stimuli, potentially reflecting different neural processes underlying early processing of verbal/semantic and visual material in memory.